Evidence in Civil Law - Spain - Mallandrich Miret, Núria (Law & Society, 2015)
This work presumes to be an introduction for the foreign reader to Spanish regulations in regard to evidence. It has been structured following a classic design in the Spanish academic literature with the aim to approach the reader to the Spanish legal way of thinking. With the same goal it a starting Chapter that analyzes the different principles that lead Spanish Civil Procedure has been included.